De musas e de transgressoras - um recorte do feminino em Chico Buarque: um enfoque sistêmico-funcional - Pinto, Fábio Ferreira (2015)
The purpose of this Master s Dissertation is the critical analysis of the image of woman in the man-woman relationship between two areas of knowledge that haven t always gone hand in hand. Literature is the art of words, so it makes sense to apply theories that come from linguistic studies to understand more deeply what underlies a literary text. Addressing the woman's representation in our literature is almost confounded with the love theme, as well as it happens in Brazilian popular music. To do so, I have the support of the Systemic Functional Linguistics (SFL) proposal, a multifunctional theory for which the language simultaneously serves three metafunctions (or meanings): Ideational (information), Interpersonal (interaction) and Textual (organizes the text according to a purpose and according to the socio-historical-cultural environment requirements). The research involves examination of the following songs: Olha, Maria (1971), by Chico Buarque, Tom Jobim and Vinicius de Moraes; Ana de Amsterdam, by Chico Buarque and Ruy Guerra (1972-1973); Mil perdões (1983), by Chico Buarque, and Cecilia (1998), by Chico Buarque. Through the theoretical framework of SFG, I relate the lexicogrammatical choices made in the microstructure of the text by the lyrics of these songs to compose this image of the woman who reveals herself in the macrostructure of discourse. Addressing women representation in our literature almost merges with the love theme, as well as it happens in Brazilian popular music. This research should answer the following questions: (a) What kind of woman vision underlies the four popular love songs? (b) How can one answer the question in (a) using SFG s metafunctions?